Prevalence and haematological parameters for bovine viral diarrhoea (BVD) in south Bengal areas in Bangladesh (Bangladesh Veterinarian, 2016)
A total of 94 blood samples were collected from commercial dairy farms, from 6 Upazillas of Barisal division. The prevalence of Bovine Viral Diarrhoea Virus (BVDV) in south Bengal areas was 51.1%, the maximum prevalence was in Ujirpur Upazilla (Sub-district; 100%) and the lowest in Pirojpur Upazilla (13.6%). There was significant (P